An attempt to obtain Bi₄Ti₃O₁₂-PVC textured ceramics-polymer composites - Nogas-Ćwikiel, E.; Bernard, H. (Condensed Matter Physics, 2013)
Bi₄Ti₃O₁₂-PVC composites were fabricated. Ceramics powders of bismuth titanate were prepared by the sol-gel method using bismuth nitrate pentahydrate Bi(NO₃)₃⋅₅H₂O and tetrabutyl titanate Ti(CH₃(CH₂)₃O)₄ as precursors. The Bi₄Ti₃O₁₂-PVC composites were fabricated from ceramics powders and polymer powders by hot-pressing method.